2020
DOI: 10.1002/alr.22668
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctivodacryocystorhinostomy (CDCR) success rates and complications in endoscopic vs non‐endoscopic approaches: a systematic review

Abstract: Background Epiphora due to refractory bicanalicular obstructions is typically managed by conjunctivodacryocystorhinostomy CDCR with or without the assistance of nasal endoscopy However the evidence for its benefit is unclear Methods A systematic review of the literature on the treatment of epiphora by CDCR was performed March All studies reporting original data on patients suffering from epiphora treated with CDCR surgery were included Primary outcomes were success and satisfaction rates Secondary outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
(623 reference statements)
1
7
0
1
Order By: Relevance
“…In our series, there were significantly more females subjected to CDCR (75%) with a mean age, similar to other studies, of 53 years 10,11 . The demographic characteristics of our cohort were consistent with the current literature 12 . Acquired NLDO is most commonly encountered in women in their 50's or older, which seems to be related to the narrowness of the bony nasolacrimal canal and the acute angle between the bony canal and the nasal floor possibly predisposing women to chronic inflammation of the nasolacrimal drainage system 13 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our series, there were significantly more females subjected to CDCR (75%) with a mean age, similar to other studies, of 53 years 10,11 . The demographic characteristics of our cohort were consistent with the current literature 12 . Acquired NLDO is most commonly encountered in women in their 50's or older, which seems to be related to the narrowness of the bony nasolacrimal canal and the acute angle between the bony canal and the nasal floor possibly predisposing women to chronic inflammation of the nasolacrimal drainage system 13 .…”
Section: Discussionsupporting
confidence: 88%
“…This subgroup underwent primary CDCR (p = 0.011) significantly more often, most likely due to a lack of evidence of concurrent disease on which to intervene to resolve the underlying cause. In a recent systematic review published by Eisenbach et al 12 on 54 articles and 2372 patients, the authors reported a similar distribution among the different aetiologies, although our group did not include any case of post-traumatic or cancer related stenosis. In our retrospective study, we decided to employ NLDO-SS to assess patient satisfaction after an anatomically and surgically successful CDCR procedure.…”
Section: Discussionmentioning
confidence: 52%
“…All the treatments described for proximal obstruction of the lacrimal pathway are generally performed by an ophthalmic plastic surgeon and the collaboration with an ENT is not always mandatory. However, conjunctivodacryocystorhinostomy is an approach in which the otolaryngologist can be helpful, since endoscopic assessment of the nasal cavity allows easy visualization of the correct position of the lacrimal tube and implementation of nasal co-interventions during the approach 20 . Nevertheless, these rules concern benign lesions since malignant ones require close collaboration with the ENT surgeon: in fact, even if a primary malignancy of the proximal lacrimal tract is rare, stenosis of the lacrimal pathway secondary to extrinsic compression due to sino-nasal, or-bital and cutaneous malignancy can occur and needs to be treated in a multidisciplinary manner in order to eradicate the tumor and re-establish functional eye to nose tear flow.…”
Section: Proximal Lacrimal Obstructionsmentioning
confidence: 99%
“…Для создания сообщения между медиальным углом глаза и носовой полостью обычно используют постоянные интубационные устройства для поддержания сформированной фистулы, например трубку Лестера Джонса. Одной из распространенных трудностей в такой процедуре является неправильное расположение конца трубки в полости носа, поэтому оториноларинголог играет важную роль в обеспечении ее правильного размещения [20].…”
Section: лечениеunclassified